Direct Measurement of the Isomerization Barrier of the Isolated Retinal Chromophore. (July 2015) - Dilger, Jonathan; Musbat, Lihi; Sheves, Mordechai; Bochenkova, Anastasia V; Clemmer, David E; Toker, Yoni
Synopsis: Energy barrier Heights for isomerization of the isolated retinal chromophore were measured using two stages of ion mobility spectroscopy (IMS-IMS).